Opioid exposure in haemophilia patients is common and underreported. Issue 2 (26th February 2020) - Peltier, Skye J.; Mazepa, Marshall A.; Freese, Rebecca L.; Nelson, Shannon F.; Kearney, Susan L.; Reding, Mark T.
Abstract: Introduction: In an era of increased opioid awareness, data on opioid exposure in haemophilia patients are lacking. Aim: The objectives of this study were to (a) provide a detailed description of opioid exposure in haemophilia patients based on written prescription data, (b) compare our findings to national haemophilia‐specific and general population datasets and (c) identify predictors of opioid exposure in haemophilia patients. Methods: Medical records of 183 adult and 135 paediatric patients from two haemophilia treatment centres (HTC) were reviewed over a 42‐month period. Chronic exposure and acute opioid exposure were recorded, and results were compared to national haemophilia (ATHNdataset) and general population (CDC) data. Results: We found that 56% of adult and 21% of paediatric patients were exposed to opioids, rates substantially higher than reported in the ATHNdataset (6%) and national population data from the CDC. In adults, but not children, severity of haemophilia was a significant predictor of opioid exposure. Most acute opioid prescriptions were not written by the HTC. Conclusions: This is the first study in the haemophilia population to examine opioid exposure based on prescription data. Opioid exposure was more common than predicted in both adult and paediatric study populations and was most often prescribed for acute pain or procedures by non‐HTC providers. Haemophilia treatment centres need to take the lead in assessing pain in haemophilia patients, guiding treatment promoting non‐opioid options, strengthen efforts to monitor opioid exposure and collect data on pain treatment in the haemophilia population.